Exploring the use of educational psychology consultation practices to sustain professional learning and behaviour - Taylor, Lisa (2017)
Background: There are many models of consultation in educational psychology literature, many of which provide a practical problem-solving framework or approach. The theory behind these frameworks is not always explicitly linked to what is done and why during consultation. An explicit theory linked to consultee’s learning, behaviour and motivation has the potential to make consultation and professional learning for staff more purposeful and effective. Aim: The main aim of this research was to explore the use of a theoretical consultation framework called Exceptional Professional Learning (EPL) in educational psychology practice. This research sought to develop a practical framework to implement the theoretical framework during consultation and to investigate the processes/mechanisms used by consultants and consultees to support internalised and sustained learning and motivation. Design: This research used an instrumental multiple-case study design. Consultations took place within four schools to support the implementation of emotion coaching using EPL. The main focus of this research was the implementation of the EPL components (autonomy, relatedness, responsiveness, authenticity and equity) during consultation to investigate the processes and mechanisms that occurred within each setting. Consultations were recorded and transcribed then the framework approach was used to analyse the results in each case study before mapping and interpreting across all case studies. Findings/conclusion: Many processes/mechanisms were consistent across all the case studies, such as the EP actively listening, nurturing relationships, acknowledging, reassuring and containing feelings in the relatedness component. The consultees would empathise, encourage, value one another’s ideas and engage in joint problem solving. Returning to the practical framework it was then possible to structure an EPL consultation session, to link it to theories of learning and motivation through the EPL components and to be clear about the consultant’s and consultee’s role through the processes and mechanisms employed.